MORPHO-FUNCTIONAL CHANGES OF CARDIOVASCULAR SYSTEM IN METABOLIC SYNDROME BY ULTRASOUND - Мустафаева Айнур Гамлет кизи (World of Medicine and Biology, 2017)
Objective – to analyze the morphofunctional characteristics of cardiovascular system in patients with signs of metabolic syndrome by echocardiography. Methods. From 2013 to 2016 364 prospectively examined patients at the age from 20 to 80 years (200 men and 164 women) with newly diagnosed MS. Patients were divided into groups according to age from 20 to 40 years 104 patients 41-60 years - 131 to the patient, 61 years of age, 129 in patients. The study included individuals who had different manifestations of MS: abdominal obesity (AO), arterial hypertension (AH), impaired glucose tolerance (IGT) and/or diabetes mellitus type II (T2DM), dyslipidemia (DLP). Results. Patients of age group 61-80 years the increase in medium size PL (4,1±0,2 mm.), KDO (148,1±10,7 ml), thickness of IVS (1,26±0,11 cm), ssli (1,26±0.12 cm), and myocardial mass of left ventricle (240,3±15.4 g), relative to similar indicators of the patients age groups 41-60 years and 20 to 40 years. Systolic parameters of the left ventricle of the examined persons from the older age group was significantly lower than in the first and second age groups, the EF value was 52.8±5.2 m. Comparison of the studied morphofunctional heart indices of the second and the first group showed that individuals aged 20 to 40 years changes in echocardiographic indicators were less pronounced. Patients of age group 41-60 years was significantly higher the average size of the left atrium. Conclusion. Given the presence of normal geometry of the myocardium in persons with obesity, it remains under-explored question of what determines the realization of these factors in a particular patient and whether the action directly or via additional metabolic markers that accompany obesity.